Landscape utilisation by an introduced pack of African wild dogs (Lycaon pictus) in eastern Botswana - Mottram, Phoebe (Department of Biological Sciences, 2019)
African wild dogs (Lycaon pictus) are one of the most endangered carnivores in southern Africa. Direct persecution, prey decline and habitat loss and fragmentation all contributed to a rapid decline in this species’ population size and distribution during the 20th century. Following a thorough population viability analysis in the late 1990s the decision was taken to manage the South African population as a metapopulation. This involved the reintroduction of packs to small, fenced protected areas and the subsequent transfer of individuals or small groups between reserves to avoid inbreeding. A key component of successful metapopulation management is post-release monitoring to provide data on the determinants of reintroduction success and failure, particularly when establishing new populations. This study aimed to provide information on the post-release behaviour and movements of a pack of eight African wild dogs introduced to the Northern Tuli Game Reserve in eastern Botswana in February 2017. Two individuals from the introduced pack were fitted with GPS collars. A total of 933 GPS locations were recorded between February 2017 and October 2017. Movement data was used to analyse home range, habitat resistance and resource utilisation by this pack across a range of spatial and temporal scales. Monthly 95% kernel density estimations revealed a mean home range of 330.02 km2 . A reduction in home range size to 37% of the average monthly 95% kernel density estimations revealed that the pack commenced denning in May 2017. However, this denning attempt failed, as shown by the home range size increasing only a month after it initially contracted, which is less than the expected contraction period required to produce a successful litter. Habitat resistance analysis revealed that the pack readily crossed fences but not rivers, with the Limpopo river serving as a very hard barrier that consistently deflected pack movement parallel to its course. Resource utilisation functions showed a preference for sites far from riverine areas, with low elevation and rough and rocky terrain. I propose that this may reflect a predator avoidance pattern, with lions (Panthera leo) in particular preferring riverine habitat with a less rough terrain in this area. The persistence of this pack in the landscape nine months post-release indicates that this reintroduction has been a partial success. Large perennial rivers provide important barriers to the movement of this pack and may thus be important for mitigating local human-wild dog conflict. Fences, however, were readily traversed and therefore communities outside of fenced areas are likely to experience conflict with this pack and any future packs re-introduced to this area.